A dipeptide‐based superhydrogel: Removal of toxic dyes and heavy metal ions from waste water. Issue 1 (January 2017) - Nandi, Nibedita; Baral, Abhishek; Basu, Kingshuk; Roy, Subhasish; Banerjee, Arindam
Abstract: A short peptide‐based molecule has been found to form a strong hydrogel at phosphate buffer solution of pH 7.46. The hydrogel has been characterized thoroughly using various techniques including field emission scanning electron microscopy (FE‐SEM), wide angle powder X‐ray diffraction (PXRD), and rheological analysis. It has been observed from FE‐SEM images that entangled nanofiber network is responsible for gelation. Rheological investigation demonstrates that the self‐assembly of this synthetic dipeptide results in the formation of mechanically strong hydrogel with storage modulus ( G ′) around 10 4 Pa. This gel has been used for removing both cationic and anionic toxic organic dyes (Brilliant Blue, Congo red, Malachite Green, Rhodamine B) and metal ions (Co 2+ and Ni 2+ ) from waste water. Moreover, only a small amount of the gelator is required (less than 1 mg/mL) for preparation of this superhydrogel and even this hydrogel can be reused three times for dye/metal ion absorption. This signifies the importance of the hydrogel towards waste water management. Abstract : Self‐assembly of a short peptide in physiological pH 7.46 forms a superhydrogel and this gel shows efficient removal of both cationic and anionic toxic organic dyes (Brilliant Blue, Congo red, Malachite Green, Rhodamine B) and metal ions (Co 2+ and Ni 2+ ) from waste water in an eco‐friendly way.